The control of alternative splicing by SRSF1 in myelinated afferents contributes to the development of neuropathic pain - Hulse, Richard P.; Drake, Robert A.R.; Bates, David O.; Donaldson, Lucy F. (Elsevier, 2016)
Neuropathic pain results from neuroplasticity in nociceptive neuronal networks. Here we demonstrate that control of alternative pre-mRNA splicing, through the splice factor serine-arginine splice factor 1 (SRSF1), is integral to the processing of nociceptive information in the spinal cord. Neuropathic pain develops following a partial saphenous nerve ligation injury, atwhich time SRSF1 is activated in damaged myelinated primary afferent neurons, with minimal found in small diameter (IB4 positive) dorsal root ganglia neurons. Serine arginine protein kinase 1 (SRPK1) is the principal route of SRSF1 activation. Spinal SRPK1 inhibition attenuated SRSF1 activity, abolished neuropathic pain behaviors and suppressed central sensitization. SRSF1 was principally expressed in large diameter myelinated (NF200-rich) dorsal root ganglia sensory neurons and their excitatory central terminals (vGLUT1 + ve) within the dorsal horn of the lumbar spinal cord. Expression of pro-nociceptive VEGF-Axxxa within the spinal cord was increased after nerve injury, and this was prevented by SRPK1 inhibition. Additionally, expression of anti-nociceptive VEGF-Axxxb isoforms was elevated, and this was associated with reduced neuropathic pain behaviors. Inhibition of VEGF receptor-2 signaling in the spinal cord attenuated behavioral nociceptive responses to mechanical, heat and formalin stimuli, indicating that spinal VEGF receptor-2 activation has potent pro-nociceptive actions. Furthermore, intrathecal VEGF-A165a resulted in mechanical and heat hyperalgesia, whereas the sister inhibitory isoform VEGF-A165b resulted in anti- nociception. These results support a role for myelinated fiber pathways, and alternative pre-mRNA splicing of factors such as VEGF-A in the spinal processing of neuropathic pain. They also indicate that targeting premRNA splicing at the spinal level could lead to a novel target for analgesic development.